A Tale of Two Metaphors: A Narrative Take on the Canadian Constitution - Cloutier, Étienne (McGill Law Journal / Revue de droit de McGill)

(untitled) (McGill Law Journal / Revue de droit de McGill, 2019)
This article sheds light on the fundamental role that narratives and metaphors play in shaping how we think, talk, and argue about the Canadian Constitution.More specifically, the article makes the case that two competing types of metaphors—dynamic and static—largely fashion Canadian constitutional law. The influential metaphors of the “living tree” and “constitutional architecture” represent prime examples of these central conceptual categories.This article argues that each of these categories stands for different views of the Constitution and, as such, influences the types of stories we tell about it. The case studies undertaken here show that each metaphor sustains dominant narratives about the Constitution, narratives whose structure mostly correspond to the archetypal “birth” and “rescue” stories.As narratives and metaphors influence our cognition and help us reason about abstract concepts and ideas (a large part of our work as jurists) we would be wise to pay closer attention to them. This article is a call, in short, for greater narrative awareness.